2016
DOI: 10.1007/s00404-016-4105-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between uterine volume and discontinuation of treatment with levonorgestrel-releasing intrauterine devices in patients with adenomyosis

Abstract: The rate of treatment failure after LNG-IUD insertion for the patients with adenomyosis was related to the uterine volume. Specifically, the treatment failure rate of large volume uterus (>150 mL) with LNG-IUD was significantly higher than that of small volume uterus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…On the other hand, uterine volume decreased significantly in the first 6 months of using Mirena and continues to decrease significantly over the 1 st and 2 nd year -the period of the study. This result was in agreed with Lee et al who showed that mean uterine volume decreased in patients with adenomyosis 6 months after Mirena insertion as well as it shows significant improvement in the VAS and PABC scores [22]. However, Cho et al study revealed that the efficacy of the LNG-IUS on uterine volume may begin to decrease in 2 years after its insertion [14].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…On the other hand, uterine volume decreased significantly in the first 6 months of using Mirena and continues to decrease significantly over the 1 st and 2 nd year -the period of the study. This result was in agreed with Lee et al who showed that mean uterine volume decreased in patients with adenomyosis 6 months after Mirena insertion as well as it shows significant improvement in the VAS and PABC scores [22]. However, Cho et al study revealed that the efficacy of the LNG-IUS on uterine volume may begin to decrease in 2 years after its insertion [14].…”
Section: Discussionsupporting
confidence: 85%
“…The current study shows a success rate of 80.4% and the failure rate of 19.6% (9 patients out of 46 patients -8 of them had expulsion of the device, and one showed failure of response) and duration of ≤6 months best time to predict failure after LNG-IUD insertion. Lee et al study showed a failure rate of about 21.6 % and median time to failure was 6.7 months [22]. Merki-Feld et al [23] and Socolov et al [24] showed 15% and 10.7% failure rate, respectively, and that decreased within 1 year after LNG-IUD insertion.…”
Section: Discussionmentioning
confidence: 96%
“…The severity of pain may be related to the degree of depression and anxiety, present in 90% of women with endometriosis, namely with AM, this is why all hormonal drugs must be prescribed in the way excluding neurotic disorders (such as depression and anxiety). Some authors indicate that depression is a direct consequence of chronic pelvic pain, but there is no consensus on this temporal issue when defining which condition precedes the other [7]. However, it is possible to affirm that the two conditions coexist, and that one worsens the experience of the other [8].…”
Section: Discussionmentioning
confidence: 98%
“…These agents create a hypoestrogenic (GnRH agonists, AIs), hyperandrogenic (danazol, gestrinone), or hyperprogestogenic (OCs, progestins) environment, with suppression of endometrial cell proliferation [6]. However, medical treatments are symptomatic and not cytoreductive: lesions survive the use of any drug, at any dose, for any length of time, and are ready to resume their metabolic activity at treatment discontinuation [7]. Medical treatments of pelvic pain caused by AM may represent hormonal therapies but are associated with adverse events impacting long-term use and adherence this is why the use of drugs with minimal systematic side effects is the target basis of the modern therapy of pelvic pain associated with AM.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have reported that long-term exposure to intrauterine levonorgestrel affects menstrual bleeding and may promote dysmenorrhea, 14,20 we have described that LNG-IUS was effective for treating menorrhagia and dysmenorrhea in perimenopausal women with benign gynecological diseases, such as adenomyosis, leiomyoma, endometrial polyp and endometriosis. 21,22 LNG-IUS treatment for the patients with endometriosis who also have accompanying adenomyosis was presently as effective as dienogest treatment for pain control. LNG-IUS might be an effective option for the treatment for the patients with endometriosis and concomitant adenomyosis.…”
Section: Discussionmentioning
confidence: 99%